Laboratory evaluation of calcareous sand specimens with inclined sedimentary surfaces - An, Yongning; Liu, Hongjun; Dong, Tong; Liu, Chao; Zhang, Minsheng (Frontiers in Built Environment, 2024)
Sedimentary processes often produce natural and blown calcareous sands that are deposited in inclined and layered formations. These calcareous sands frequently exist in a complex stress state with rotating principal stress axes that result in intricate mechanical properties. To investigate the mechanical behaviors of calcareous sands with inclined sedimentary surfaces, we developed a device to prepare hollow cylindrical specimens from artificially crushed calcareous sands. By combining this device with a hollow cylindrical torsional shear apparatus, undrained monotonic loading and pure principal stress rotation tests were conducted to investigate the static and dynamic properties of the inherently anisotropic calcareous sands. The results indicate that the shear dilatancy property is related to the principal stress direction; the shear dilatancy of calcareous sand decreases as the direction of the principal stress increases, and the peak stress ratio decreases with increasing principal stress direction and increases with increasing deposition direction. In the precyclic loading period, increases in the deposition direction led to increases in the stabilities of the specimens and decreases in excess pore pressure accumulation, which further affect the dynamic shear modulus and damping ratio of the calcareous sand. In the late stage of cyclic loading, the inherent anisotropies of the specimens are destroyed, so that the excess pressure and hysteresis loop characteristics start to converge.